2018
DOI: 10.2215/cjn.05580517
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the Nephrology In-Training Examination and ABIM Nephrology Certification Examination Outcomes

Abstract: American Society of Nephrology In-Training Examination performance is significantly associated with American Board of Internal Medicine Nephrology Certification Examination score and passing status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This suggests that, despite correlations between ITE and board performance, prediction of board examination pass/fail using the ITE for an individual resident is of little practical benefit. 26 Even residents who perform very poorly on the ITE have a reasonable likelihood of passing their board examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that, despite correlations between ITE and board performance, prediction of board examination pass/fail using the ITE for an individual resident is of little practical benefit. 26 Even residents who perform very poorly on the ITE have a reasonable likelihood of passing their board examination.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] Eleven of the 12 studies using linear regression found that ITE scores significantly predicted board examination performance. 4,7,9,10,13,[25][26][27][28][29] Only 1 study showing signicant prediction for PGY-3-PGY-4 residents, but not PGY-1-PGY-2 residents (Swanson et al, orthopaedic surgery 21 ). For logistic regression analysis, studies either used ITE scores as a predictor on a continuous scale or categorized ITE scores into 2 categories (eg, , 10th percentile, .…”
Section: Relationship To Other Variables' Validity Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…(2) to determine interrater scoring agreement between programs and WRNMMC investigators; (3) to determine overall and scenario pass percentages and mean scores, hypothesizing that second-year fellows (third-years analyzed as second-years) would perform better than first-year fellows, and fellows in programs testing in 2016 would improve in 2017, and perform better than those at programs administering the test for the first time; (4) to identify evidence-based questions incorrectly answered by .50% of second-year fellows; (5) to determine fellow satisfaction with the OSCE as a formative evaluation tool; (6) to determine whether OSCE score correlated with in-training examination score for second-year fellows (3,18).…”
Section: Fellow Testingmentioning
confidence: 99%
“…The practice of using formative testing tools, such as standardized in-training examinations, is integrated across graduate medical education programming as a means of resident and program assessment. In addition, performance on these examinations have demonstrated varying degrees of correlation to future board certification examinations in a host of physician programs such as internal medicine, family medicine, pediatrics,infectious disease, rheumatology, cardiology, nephrology, and several others 9,10,[15][16][17][18][19][20][21]. The framework for this study, CBAM, was created as a way for education specialists to understand how teachers were implementing new innovations and strategies into the classroom and to research how the successes demonstrated in educational research may not carry into practice; the fidelity -or adherence to the original plan-was lost when transitioning from a controlled environment to real-world practice 22,23.…”
mentioning
confidence: 99%